Single-cell sequencing decodes the secrets of the RAP phenomenon of corticotomy - Fan, Zhibo; Li, Shenghong; You, Liping; Lan, Yuxin; Zhong, Yutong; Ma, Yuefan; Xu, Jie; Xu, Xiaomei (Frontiers in Immunology, 2024)
Introduction Corticotomy-assisted tooth movement is commonly performed in clinics, however, its time-limited efficacy and the fear of surgery among patients significantly limit its clinical application. Hence, researchers have investigated non-invasive methods to accelerate tooth movement. However, the molecular mechanisms underlying corticotomy-assisted tooth movement are not fully understood. Methods Micro-CT and TRAP stain were used to tooth movement and bone resorption. Single-cell RNA sequencing was used to study the transcriptome heterogeneity of macrophages after corticotomy. Transmission electron microscopy and iron ion detection was used to evaluate ferroptosis and iron metabolism. In addition, we carried out immunohistochemistry, quantitative real-time and flow cytometry verify the effect of iron on macrophage polarization. Results Single-cell RNA sequencing of digested alveolar bone identified a significant increase in iron metabolism-related genes post-corticotomy. Macrophages play a central role in this field. Following the dimensionality reduction of macrophages, we revealed a new developmental state via pseudotime analysis post-corticotomy. SCENIC analysis revealed that Atf3 is a key transcription factor influencing this new state. We found that Atf3+ macrophages were closely associated with osteoclasts. Moreover, cell chat revealed an increase in cellular communication between Atf3+ macrophages and other cell types after corticotomy. Discussion These findings suggested that Atf3+ macrophages might play a key role in corticotomy-accelerated tooth movement, thus providing potential targets for drug development.